THE RELATIONSHIP BETWEEN PARENTING STYLE AND CHILDREN'S DEVELOPMENT AGED PRE-SCHOOL - Amilia krisdiantini; Bagus Setyoboedi; Ilya Krisnana (UNIVERSITAS AIRLANGGA, 2020)
Background: Development is related to the increase in the structure of bodily functions which Include tge ability of gross and fine motor skill, languange, and socializationand independence. One of the factors that influence a child's development is parenting, which is the pattern of interaction between parents and children. Early detection of development needs to be done in order to know deviations in development. Method: This research method used an observational analytic cross-sectional study design. The number of samples was 69 toddlers with a sampling technique using purposive sampling. The independent variable is parenting and the dependent variable is child development. The instruments used were parenting questionnaire and child development questionnaire, namely KPSP. Data analysis technique used was the spearman with α = 0.05 and the analysis of the closeness of the two relationships using correlation coefficient. Results: The results showed that there were 33.3% of respondents with permissive parenting had developmental status in accordance with or normal with their age, parents with democratic parenting also had 53.7% of respondents whose development was in accordance with or normal with their age, while authoritarian parenting there are 40.0% of respondents who are appropriate or normal for their age. Spearmen test results are known for each parenting, namely permissive parenting with p value 0.928, democratic parenting with p value 0.023, and authoritarian parenting with p value 0.420. Conclusion: the data shows that there is a relationship between parenting and developmental patterns, those are democratic parenting and permissive parenting.Keywords: child development, parenting, toddlers